2007
DOI: 10.3846/16486897.2007.9636917
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Chemical Indication of Roadside Ecotone Zones

Abstract: A public motor road net crossing forest complexes influences the natural environment to a very high degree. Soils in roadside forest ecotone zones constitute a certain filter buffering chemical contamination generated by motor traffic. The aim of the paper is to present the methods of identification of transport contaminants influencing the roadside stand condition. The results of monitoring roadside ecotone zones indicate the necessity of applying such technical appliances as oil‐derivative separators, filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…However, the plantain peels used for this research were harvested in a farm located in a small town far away from commercial and industrial activities with little or no vehicular movements/emissions. This is justifiable as literature has proven that vehicular emissions are associated with and even described as 'first line sources' of heavy metal pollutants (Poszyler-Adamska and Czerniak, 2007). Also, lead, cadmium and nickel have been reported as the most prevalent heavy metals pollutant in vehicular emission due to their presence in fuel as anti-knocking agents (Suzuki et al, 2009;Atayese et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, the plantain peels used for this research were harvested in a farm located in a small town far away from commercial and industrial activities with little or no vehicular movements/emissions. This is justifiable as literature has proven that vehicular emissions are associated with and even described as 'first line sources' of heavy metal pollutants (Poszyler-Adamska and Czerniak, 2007). Also, lead, cadmium and nickel have been reported as the most prevalent heavy metals pollutant in vehicular emission due to their presence in fuel as anti-knocking agents (Suzuki et al, 2009;Atayese et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…These activities send trace metals into the air and the metals subsequently deposited into nearby soils, which are absorbed by plants on such soils. Public motor roads affect natural environment to a large extent because automobiles act as line sources of heavy metal pollutants (Poszyler-Adamska & Czemiak, 2007). Samples of soil from lands near motorways in some urban cities in Nigeria such as Jos, Osogbo, Ibadan and other cities, have been studied (Abechi, et al, 2010;Fakayode & Olu-Owolabi, 2003;Onianwa, 2001; Ihenyen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…They can also migrate to surface and ground waters and spread in great distances, re-enter food chains and poison live organisms (Vosylienė et al 2010). Heavy metals can both migrate and accumulate within soil, often disturbing soil processes and sometimes causing soil degradation (Baltrėnas, Vaišis 2006;Poszyler-Adamska, Czerniak 2007). The migration and accumulation of heavy metals in soils depends on several environmental factors, such as meteorological conditions, the chemical and mineralogical composition of soil-forming rocks, the textural composition of the soil, soil solution pH, sorption, and the amount of the soil organic matter (Johnson et al 2011).…”
mentioning
confidence: 99%
“…introduction ecological studies have shown significant exposure-response relationships for adverse pollution effects in association with particulate mass concentrations (Poszyler-Adamska, Czerniak 2007;staniūnas et al 2010). Particulate matter has been associated with pollution and fate in urban storm water (Valentukevičienė, ignatavičius 2011).…”
mentioning
confidence: 99%